The distance preschool education during the COVID-19 pandemic - Galván Dueñas, Flor de María (2022)
The objective of the study is to understand the challenges and perspectives of distance preschool education during the COVID-19 pandemic. A descriptive systematic review was carried out that included 13 articles extracted from the databases: SCOPUS, ProQuest, SciELO and EBSCO. The following keywords were included as a search strategy: “preschool teacher”, “pandemic”, “distance education”, “online learning”, “computer-assisted teaching”. It was concluded that the pandemic has presented challenges for entry-level teachers. The interaction processes of preschool teachers vary in the different contexts in which they serve during this pandemic. Teacher training and development must include the knowledge, skills and dispositions necessary to reconsider and participate successfully in distance teaching and learning. This training should be comprehensive and also include how to work with parents.